Meaningful Work: Viktor Frankl's Legacy for the 21st Century - von Devivere, Beate (Springer International Publishing, 2018)
This book offers meaningful work as one of the most relevant issues for 21st century workplaces, and organizations seeking to develop leadership and drive positive change. It uses Viktor Frankl's legacy as a scientific and philosophical pioneer, while combining cutting edge research findings from the behavioural sciences, organizational and management research, and human resource development with outstanding examples of new work approaches of leadership from around the globe. In order to respond to 21st century demands on meaningful work, this book harnesses the power of living meaning, values, purpose and compassion in workplaces. Beate von Devivere shows managers, human resources experts, consultants, coaches, medical experts, students and counsellors as well as all dedicated individuals, how to find meaning in their organizations, their teams and individual functions and challenges, bringing Viktor Frankl's approach to today's workplaces. Integrating a wide range of knowledge and expertise, this book covers organizational development, management practice, and findings from psychology, neuroscience as well as therapeutic approaches and new work concepts. Meaningful work is promoting an integrated approach for the 'Copernican turn', further promoting meaningful work, purpose and a good life.